Nutritional rickets among children of Northern Kerala, India - Jose, Soumya; A., Bindu (International Journal of Contemporary Pediatrics, 2017)
Background: Vitamin D deficiency is a very common micronutrient deficiency in our country and ranks among the 5 most common disease in children worldwide. Methods: To study the presentation and predisposing factors of rickets among children in Northern Kerala. Results: This study was conducted in the department of Pediatrics in a tertiary care hospital in Northern Kerala. Nutritional rickets diagnosis was based on clinical, radiological and biochemical parameters and appearance of provisional zone of calcification after vitamin D therapy. Data was analyzed and presented as percentage and mean. Student t-test was used for statistical analysis of the results. Conclusions: A total of 54 children having a variety of clinical presentations of rickets were seen during the study period. There were 46.3% males and 53.7% females. The mean age of diagnosis was 24 months.70.4% children were exclusively breast fed up to 6 months. None of the breast-fed infants had received vitamin D supplementation according to current guidelines. 66.7% children were not exposed to sunlight. Rickets was commonly found in children with no protein energy malnutrition. Genu varum and wrist widening were the most frequent clinical features observed in 92.6% patients. The radiological and biochemical characteristics of cases were ascertained before and after therapy. The biochemical changes were analyzed by student (t) test. There was a significant decrease in the ALP activity after vitamin D therapy (P= 0.000). Out of these 54 children with rickets 47(87.03%) responded to treatment with vitamin D3 and 7 (12.96%) were resistant to treatment with vitamin D3.